Meningkatkan Hasil Panen Dan Ketahanan Pangan Di Desa Bagik Payung Selatan Melalui Pemberdayaan Masyarakat Dengan Pemanfaatan Pupuk Trichokompos - Shaqinah, Alya; Azmi, Muhammad Khairul; Atsmari, Rizki Prapitri; Akbar, Zulfikar Ibnu Ali; Iemaaniah, Zuhdiyah Matienatul (Universitas Mataram, 2024)
Bagik Payung is one of the villages located in Suralaga Sub-district, East Lombok , West Nusa Tenggara . The village has an area of 1,606.47 km2 with a population of 4,456 inhabitants. The majority of the population of Kunden Village is male with a percentage of 51%, and 49% female. The majority of occupations in Kunden Village are farm laborers with a percentage of 28%, employees at 26%, self-employed at 19%, farmers at 17%, carpenters at 5%, retirees at 4%, and services at 1%. The high percentage of farm laborers is certainly a concern for the local village government. Therefore, through the community service program, the PKL Group of the Agricultural Extension Unit (UPT) seeks to improve the knowledge and skills of the community. One of the programs carried out to improve community knowledge and skills is Training in Making Trichocompost Fertilizer and Liquid Organic Fertilizer.